Labour Analgesia - Rabindran Chandran; D Sharad Gedam (International Journal of Medical Research and Review, 2017)
Regional anaesthesia is nowadays commonly practised universally. It provides superior pain relief in first & second stages of labour, anesthesia for episiotomy & instrumental delivery.